2011
DOI: 10.1007/s00404-011-2097-1
|View full text |Cite
|
Sign up to set email alerts
|

A review of the problematic adhesion prophylaxis in gynaecological surgery

Abstract: BackgroundAdhesions lead to considerable patient morbidity and are a mounting burden on surgeons and the health care system alike. Although adhesion formation is the most frequent complication in abdominal and pelvic surgery, many surgeons are still not aware of the extent of the problem. To provide the best care for their patients, surgeons should consistently inform themselves of anti-adhesion strategies and include these methods in their daily routine.MethodsSearches were conducted in PubMed and The Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 59 publications
0
68
0
2
Order By: Relevance
“…In further course, adhesion formation must be regarded as the most common complication occurring after 60% -90% of procedures [5]- [7]. Adhesions are responsible for a long list of sequelae ranging from the most frequent one, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In further course, adhesion formation must be regarded as the most common complication occurring after 60% -90% of procedures [5]- [7]. Adhesions are responsible for a long list of sequelae ranging from the most frequent one, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…More severe adhesions occur with increasing numbers of cesarean section. In such cases, additional adhesiolysis might be required during surgery and this could extend the operative time along with the increased possibility of more blood loss and prolonged hospital stay [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Overall, 20 to 40 % of infertility cases are secondary to APA. 17,18 Studies in SSA showed that fibrosis, particularly through APA, ranked first in etiologies of secondary female infertility [19][20][21] which is the most common type in this part of the world. 19,22 Women experiencing the drama of infertility generally present with tubal factor infertility 20,21 requiring expensive therapies.…”
Section: The Burden Of Adhesions In Sub-saharan Africamentioning
confidence: 99%